White Root Fungus Capability (Rigidoporus microporus (Swartz: Fr.) Van Ov.) in Degrading Cellulose Waste - Putri, Dianty; Nasir, Nasril; Agustien, Anthoni (Metamorfosa: Journal of Biological Sciences, 2019)
Cellulose is one of abundance natural biopolymer with limited usage. The common found waste cellulose are waste straw, sawdust, and pineapple pit. R igidoporus microporus is a white root fungi groups that often attack the roots of plants that rot and die. This study was conducted to assess the ability of white root fungi ( R. microporus ) to degrade waste cellulose, according to cellulolitic activity index of potential R. microporus isolate. The medium used was Carboxy Methyl Cellulose (CMC) with dye Congo Red (0,1%). The results obtained that R. microporus has cellulotic index 3,23 which indicated as potential cellulose degrade.